2010
DOI: 10.17221/147/2009-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lead on seedling growth of spesia populnea

Abstract: The effects of lead on root, shoot and seedling length, leaf area, number of leaves, plant circumference, seedling dry weight, root/shoot and leaf area ratios of Thespesia populnea L. were determined in greenhouse under natural environmental conditions with and without phytotoxic metal ions at 5, 10, 15, 20, and 25 µmol/l. Lead treatments have a strong influence on the growth and development of T. populnea by reducing significantly (P < 0.05) all the above parameters. Lead treatment at 5-25 µmol/l produced sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
3
24
0
2
Order By: Relevance
“…Patra et al (2004) described that plant species/genotypes showed differences in tolerance to heavy metal depending on number of metacentric or diploid chromosomes and total length of diploid complement. The other reason can be differential physiological association of tolerance mechanism and growth of plants (Kabir et al, 2010). The Shaheen basmati showed better growth than KS-282 attributed to reduced Pb accumulation and possibly mobilization of the defense mechanisms including antioxidative enzymes such as superoxide dismutase, catalase, guaiacol peroxidase, ascorabte peroxidase and glutathione reductase (Pourrut et al, 2011), which might suppressed the Pb transport to further tissues (Sekara et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Patra et al (2004) described that plant species/genotypes showed differences in tolerance to heavy metal depending on number of metacentric or diploid chromosomes and total length of diploid complement. The other reason can be differential physiological association of tolerance mechanism and growth of plants (Kabir et al, 2010). The Shaheen basmati showed better growth than KS-282 attributed to reduced Pb accumulation and possibly mobilization of the defense mechanisms including antioxidative enzymes such as superoxide dismutase, catalase, guaiacol peroxidase, ascorabte peroxidase and glutathione reductase (Pourrut et al, 2011), which might suppressed the Pb transport to further tissues (Sekara et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…3). Other research reported that increasing Pb doses (0, 5, 10, 15, 20, 25 µm/M) caused a decrease of leaf number in Thespesia populnea L. (Kabir et al, 2010). It was reported that incremental concentrations of Cd after 0.1 µm/M caused a reduction of leaf number in tomato.…”
Section: Number Of Leaf Per Plant and Number Of Node Per Main Stemmentioning
confidence: 95%
“…Heavy metals (HM) act as essential plant micronutrients however, excess amount of these contents become toxic pollutants [1]. Beyond threshold levels, heavy metals (HM) are transformed into contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly used in fertilizers, batteries, chemicals and ceramics, in different products like pottery, gasoline, lead glass, pesticides, paints, hair dyes, rubber toys and newsprint. Major lead content in the soil comes from weathering of geological rock formations, lead mine's discharge, automobile exhausts, industrial applications, smelting operations, fertilizer impurities, use of lead arsenate in metal plating and finishing operations, tetramethyl lead applications as anti knocking agent in petrol [9] and plants obtain lead from such agencies [1]. Increase in lead concentration in cultivated soils is detected in close proximity to industrial sites.…”
Section: Introductionmentioning
confidence: 99%